2020
DOI: 10.1038/s41598-020-78675-7
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTL hotspots associated with weed competitive traits in backcross population derived from Oryza sativa L. and O. glaberrima Steud.

Abstract: To improve grain yield under direct seeded and aerobic conditions, weed competitive ability of a rice genotype is a key desirable trait. Hence, understanding and dissecting weed competitive associated traits at both morphological and molecular level is important in developing weed competitive varieties. In the present investigation, the QTLs associated with weed competitive traits were identified in BC1F2:3 population derived from weed competitive accession of O. glaberrima (IRGC105187) and O. sativa cultivar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…The quantile-quantile (Q-Q) plot also confirmed the detected associated markers with the growth parameters in rice ( Figure 9 ). Marker–trait associations have been reported previously by many workers in rice [ 24 , 30 , 64 ].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The quantile-quantile (Q-Q) plot also confirmed the detected associated markers with the growth parameters in rice ( Figure 9 ). Marker–trait associations have been reported previously by many workers in rice [ 24 , 30 , 64 ].…”
Section: Discussionmentioning
confidence: 73%
“…The associations were at 300 cM position on chromosome 4; 159 and 221 cM on chromosome 6; and 27 cM position on chromosome 8. Bharamappanavara et al [ 64 ] reported a QTL on chromosome 2 at 61.59–115.44 cM position and on chromosome 3 within 16.95 cM. However, no reports are available for the locations detected by us for QTLs controlling AGR in rice.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, weed-suppressive strategies and control methods employed in IWM are preferred. Additionally, there have been a few studies searching for QTLs for weed competitive traits in crops ( Coleman et al, 2001 ; Bharamappanavara et al, 2020 ; Dimaano et al, 2020 ). Although many of these studies have not mentioned specific genes from fine mapping, it is likely that genes involved in growth and development like maturity genes, tillering genes, and leaf development genes will be strong candidates for improvement.…”
Section: Potential Gene Targets For Reducing Weed Fitnessmentioning
confidence: 99%
“…Studies have also reported several sterility loci in interspecific crosses between O. sativa and O. glaberrima (Lorieux et al 2000;Ren et al 2005;Li et al 2008Li et al , 2018Xu et al 2014;Shen et al 2015;Yang et al 2016). Further, there are reports of quantitative trait loci (QTLs) derived from O. glaberrima associated with grain quality (Li et al 2004;Wambugu et al 2018), rice stripe necrosis (Gutiérrez et al 2010), iron toxicity (Dufey et al 2015) and competitiveness against weeds (Bharamappanavara et al 2020). Molecular profiling of interspecific progeny of O. glaberrima has been performed (Semagn et al 2007;Ndjiondjop et al 2008;Bimpong et al 2011;Agnoun et al 2012;Moukoumbi et al 2015) to provide insight into the extent of the O. glaberrima genome inherited in the progenies.…”
Section: Introductionmentioning
confidence: 99%
“…2010), iron toxicity (Dufey et al . 2015) and competitiveness against weeds (Bharamappanavara et al . 2020).…”
Section: Introductionmentioning
confidence: 99%